Mimetičnost v kontekstu prestopanja robov umetnostnih diskurzov v modernizmu - Jež, Andraž (Primerjalna književnost, 2015)
We can often encounter an idea about a general decline of imitation/representation in the Modernist art. The text goes again this implication, attributing to Modernism not a general relationship towards the mimetical, but, instead, a contingent examination of a traditional relationship in each of the arts' disciplines.
Keywords: književnost in glasba; modernizem; mimesis; posnemanje; reprezentacija; konkretna glasba; fotorealizem